2011
DOI: 10.1111/j.1529-8817.2011.01017.x
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and Characterization of Cyanobacteria Possessing Antimicrobial Activity From the Sundarbans, the World’s Largest Tidal Mangrove Forest1

Abstract: Eight obligately halophilic, euryhaline cyanobacteria from intertidal soil were isolated in artificial seawater nutrients III (ASN-III) medium. Antimicrobial activity, 16S rRNA gene sequences, phenotypic characters as well as growth and antibiosis in response to variable salinity, temperature, phosphate concentration, and pH were studied. Minimum inhibitory concentrations (MIC) of the extracts against Staphylococcus aureus, Escherichia coli, Bacillus subtilis, Pseudomonas aeruginosa, and multiple drug-resistan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(19 citation statements)
references
References 53 publications
1
18
0
Order By: Relevance
“…Phormidium spp. have been previously reported to produce compounds that inhibit growth of different Gram-positive and Gram-negative bacterial strains, yeasts, and fungi [40][41][42]. Butanol extracts of Lyngbya sp.…”
Section: Cyanobacterial Morphotypesmentioning
confidence: 99%
“…Phormidium spp. have been previously reported to produce compounds that inhibit growth of different Gram-positive and Gram-negative bacterial strains, yeasts, and fungi [40][41][42]. Butanol extracts of Lyngbya sp.…”
Section: Cyanobacterial Morphotypesmentioning
confidence: 99%
“…Pramanik et al . () reported the antimicrobial activity of the extracts of Cyanobacteria isolated from the intertidal soil of Sundarbans mangrove forest, which showed positive results against Bacillus subtilis and multiple drug‐resistant clinical isolates. Cyanobacterial strains isolated from microbial mats developed on the soil surface and mangrove pneumatophores were reported to produce toxins (microcystins and saxitoxins) and exhibited toxicity to brine shrimp (Mohamed and Al‐Shehri ).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, biofilm-forming Cyanobacteria in particular could be harnessed for exploiting novel low volume yet high value specialized chemicals of immense industrial applications especially pharmaceuticals, nutraceutical and cosmeceuticals. Pramanik et al (2011) reported the antimicrobial activity of the extracts of Cyanobacteria isolated from the intertidal soil of Sundarbans mangrove forest, which showed positive results against Bacillus subtilis and multiple drug-resistant clinical isolates. Cyanobacterial strains isolated from microbial mats developed on the soil surface and mangrove pneumatophores were reported to produce toxins (microcystins and saxitoxins) and exhibited toxicity to brine shrimp (Mohamed and Al-Shehri 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Cyanobacteria are emerging as an exciting resource for the discovery of new classes of therapeutics (Pramanik and Mukherjee, 2011). The current increase in scientific and commercial interest in the use of genetic resources is also of significance to international policy makers.…”
mentioning
confidence: 99%